Strategies to evaluate alginate based bioinks applying extrusion printing for biofabrication (Transactions on Additive Manufacturing Meets Medicine, 2020)
For bioprinting, tailored bioinks combining tissue-like mechanical properties, printability and high biocompatibility are needed. The strategy of this project includes the precise characterization of the synthesis route and material properties, description of the printing process, as well as computing of flow and shear stress profile inside the printing needle. Furthermore, in vitro analyses using lentiviral fluorescent reporter cells were performed, which is a novel method that has so far hardly been used in biofabrication. The evaluation of the hydrogel and printing process for successful biofabrication is a multi-stage process and in our case demonstrated that ADA-GEL is a promising bioink.
Keywords: bioprinting; reporter cells